Improving Teacher Talk To Enhance Teacher – Students Interaction (An Action Research at SMP Negeri 1 Bangun Purba) - Rosmanidar (Journal of Innovative and Creativity, 2023)
The purposes of the study were to find out the interaction pattern in the classroom during the teaching-learning activity, to find out the effort might be done to improve teacher talk and to know how to enhance teacher-students interaction through improving the teacher talk. An Action Research was conducted with the object of this study was teacher talk delivered by the teacher of SMP N 1 Bangun Purba and the interaction pattern in the teaching-learning activity at the seventh grader students of VII-4. The activity of action research consisted of planning, acting, observing and reflecting. In cycle 1, a discussion about certain material related with the teacher talk and interaction was conducted. The result of interaction in the pre cycle activity was also given in cycle 1. The same activity was conducted in cycle 2, a discussion and interaction analysis of the cycle 1 was delivered to the teacher. Those activities were done outside the classroom. An analysis instrument from Moskowitz named Foreign Language Interaction Analysis (FLINT) was used to analyze the teacher talk and the interaction. An interview and questionnaire were conducted to know the teacher and students opinion of the research. All the collected data was described qualitatively. The report of the research consisted of descriptive of some facts and events occurred during the research. The result of the research showed that the pattern of interaction was mostly started by the teacher and giving information category was the most pattern occurred. The action research phases, the given suggestions and discussion succeeded to improve the teacher talk. The teacher talk was not dominating and the students got more opportunities to interact. It was shown by the decrement of the teacher talk percentage occurred in teaching-learning activity. The teacher talk in pre cycle activity was 66.2%, 64% in cycle 1 and 57.3% in cycle 2. The teacher also succeeded to enhance the interaction in the classroom. The students become more responsive and participate actively in the teaching-learning activity. The enhancement of interaction was shown by the students‘ response. In the pre cycle the students talk achieved 28.3%, 22.5% in cycle 1 and 37.5% in cycle 2. Based on the result above, it can be concluded that the teacher talk had been improved and the interaction showed an enhancement through the students‘ response. Giving reflection to the teacher talk can improve the talk to be better and giving suggestion based on the theory of certain expert can be beneficial input to improve the teacher talk and creating interactive situation in the classroom.